The IncP-6 Plasmid p10265-KPC from Pseudomonas aeruginosa Carries a Novel ΔISEc33-Associated blaKPC-2 Gene Cluster - Dai, Xiaotian; Zhou, Dongsheng; Xiong, Wei; Feng, Jiao; Luo, Wenbo; Luo, Guangming; Wang, Haijing; Sun, Fengjun; Zhou, Xiangdong (Frontiers in Microbiology, 2016)
Pseudomonas aeruginosa strain 10265 was recovered from a patient with pneumonia in a Chinese public hospital, and it displays the carbapenem resistance phenotype due to the acquisition of a nonconjugative but mobilizable IncP-6-type plasmid p10265-KPC. p10265-KPC carries a Tn5563-borne defective mer locus and a novel ΔISEc33-associated blaKPC-2 gene cluster without paired invert repeats and direct repeats at both ends. Mobilization of this ΔISEc33-associated element in p10265-KPC would attribute to homologous recombination-based insertion of a foreign structure Tn3-ISApu1-orf7-ISApu2- ISKpn27-ΔblaTEM-1-blaKPC-2-ΔISKpn6-korC-orf6-klcA-ΔrepB into a pre-existent intact ISEc33, making ISEc33 truncated at the 3' end. The previously reported pCOL-1 represents the first sequenced KPC-producing IncP-6 plasmid, while p10265-KPC is the second one. These two plasmids carry two distinct blaKPC-2 gene clusters, which are inserted into the different sites of the IncP-6 backbone and have different evolutionary histories of assembly and mobilization. This is also the first report of identification of the IncP-6-type resistance plasmid in China.